Pendampingan pemanfaatan tanaman herbal pada pasien hipertensi dan diabetes melitus sebagai upaya pencegahan penyakit gagal ginjal di Puskesmas Gandus Palembang - Evi Lusiana; Ardesy Melizah Kurniati; Debby Handayati Harahap; Nia Savitri Tamzil; Nita Parisa; Masayu Syarinta Adenina; Ayesha Augusta Rosdah; Desi Oktariana; Pariyana Pariyana; Aida Nur Azizah; Arya Putera Islami (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2024)
Hypertension and diabetes mellitus are risk factors for chronic kidney disease. A person diagnosed with hypertension and diabetes mellitus is required to regularly take medication for life, which can lead to side effects of drugs (ESO). This triggers the search for more effective and safer drugs, so many people start to turn to traditional medicine. The main objective of this community service is to increase community knowledge and skills through assistance in cultivating herbal plants such as Sambiloto, Celery, and Ginger. The method of service carried out in this activity is by giving questionnaires before and after the delivery of material with the community in the working area of the Gandus Palembang Health Center. The targets of community service activities are hypertension and diabetes mellitus patients and the community registered in the working area of the Gandus Palembang Health Center as many as 30 participants. The results of the counseling showed that there was an increase in the results of participants who fell into the good category, according to the variables of knowledge, attitude and action respectively 56.7%, 23.3% and 40%.